Chemo- and stereoselective synthesis of E-2-(2-acyl-1-tosylvinyl)pyrroles from tosylmethyl isocyanide (TosMIC) and 2-(acylethynyl)pyrroles. (9th November 2021) - Saliy, Ivan V.; Gotsko, Maxim D.; Sobenina, Lyubov' N.; Ushakov, Igor A.; Trofimov, Boris A.
Graphical abstract: Abstract: Uniquely functionalized at the double bond with tosyl and acyl substituents, E-2-(2-acyl-1-tosylvinyl)pyrroles, are chemo- and stereoselectively formed in up to 82% yield in reaction (Et3 N/MeCN) of tosylmethyl isocyanide (TosMIC) and available 2-(acylethynyl)pyrroles.